Auf der Suche nach einem anderen Deutschland. Das Verhältnis Frankreichs zur DDR im Spannungsfeld von Perzeption und Diplomatie - Wenkel, Christian (Studien zur Zeitgeschichte, 2014)
In France, the notion of the other Germany was at once myth and model. How else do we explain France's intensive contact with East Germany? Using a broad range of sources, Christian Wenkel examines the basic specifics of France-East German relations and analyzes the genesis and evolution of ties at the economic, cultural, parliamentary, and political levels.